THE CORRELATION BETWEEN THE STUDENTS’ VOCABULARY MASTERY AND THEIR WRITING SKILL OF THE TENTH GRADE STUDENTS OF SMA NEGERI 1 KERAJAAN IN THE ACADEMIC YEAR OF 2020/2021 - Limbong, Anggraeni Etrika. U.; Lumban Raja, Viator; Sari, Anna Stasya Prima (Kairos English Language Teaching Journal, 2021)
Writing is one of the important skills in learning English that should be acquired by the students. And also it is one of the most difficult skills to the students to b acquired in the learning English. One of the reasons is the lack of students’ in vocabulary mastery. That is why this research was conducted in order to find out the correlation between students’ vocabulary mastery and their writing skill at the tenth grade students of SMA Negeri 1 Kerajaan in the Academic Year of 2020/2021 which is consist of four classes. The writer took 53 students as the sample of this research by whose students numbers are odd randomly. The instrument in collecting data is the test. The tests were used to collect the data of the students’ vocabulary mastery and their writing skill. The techniques which were used to analyze the data are normality test, Linear Regression Analysis Statistic and Pearson Product Moment by using Statistical Product and Service Solution (SPSS). The result of hypothesis test showed that the coefficient of correlation is 0,638 at the significant level 0,5%. Since the rcount is higher than rtable (0,638>0,279) it means that Ho is rejected. It can be concludedthat there is a significant correlation between students’ vocabulary mastery and their writing skill at the tenth grade students of SMA Negeri 1 Kerajaan in the Academic Year of 2020//2021.